On The Recursive Sequence x(n+1)=x(n-20)/[1+x(n-2)x(n-5)x(n-8)x(n-11)x(n-14)x(n-17)] - Burak Oğul; Dağıstan Şimşek (MANAS: Journal of Engineering)
The behaivour of the solutions of the following system ofdifference equations is examined,x(n+1)=x(n-20)/[1+x(n-2)x(n-5)x(n-8)x(n-11)x(n-14)x(n-17)]where the initial conditions are positive real numbers.The initial conditions of the equation are arbitrary positive real numbers.Also, we discuss and illustrate the stability of the solutions in theneighborhood of the critical points and the periodicity of the consideredequations.